2002
DOI: 10.1001/archinte.162.18.2125
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection With Hepatitis Viruses and Outcome of Initial Antiretroviral Regimens in Previously Naive HIV-Infected Subjects

Abstract: Clinical progression of HIV-1 disease after starting potent antiretroviral therapy is accelerated by concomitant infection with HCV. Compared with patients without coinfection, coinfected patients showed impaired CD4+ cell recovery, despite similar virologic response to HIV-1 therapy. These findings may have important implications for the treatment of HCV and for the timing of initiation of HIV-1 therapy in coinfected individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
147
4
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(181 citation statements)
references
References 36 publications
26
147
4
3
Order By: Relevance
“…In our collaborative study, information on drug use after HIV infection or treatment adherence is not collected for the majority of individual cohorts. Other factors especially prevalent in injecting drug users and associated with a poor immunological response, such as hepatitis C virus coinfection [31] or tobacco smoking [32,33], might also explain their poorer responses. Specific epidemiological surveys that appropriately measure these variables would be of value to disentangle the respective roles of different factors explaining poor response in injecting drug users.…”
mentioning
confidence: 99%
“…In our collaborative study, information on drug use after HIV infection or treatment adherence is not collected for the majority of individual cohorts. Other factors especially prevalent in injecting drug users and associated with a poor immunological response, such as hepatitis C virus coinfection [31] or tobacco smoking [32,33], might also explain their poorer responses. Specific epidemiological surveys that appropriately measure these variables would be of value to disentangle the respective roles of different factors explaining poor response in injecting drug users.…”
mentioning
confidence: 99%
“…Several studies have shown that chronic HBV infection significantly increased liver-related mortality in HIV-1-infected patients but did not have a direct impact on progression to AIDS or on viral and immunological responses to ART. [24][25][26] However, studies from Taiwan found that individuals with chronic hepatitis B were less likely to achieve HIV RNA suppression at 4 and 24 months after initiation of ART. 26,27 Overall, it is still debated whether HBV co-infection might negatively affect the efficacy of antiretroviral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study in Italy has showed increasing divergence of mean CD4 lymphocyte counts up to 36 weeks after HAART initiation between patients with and without chronic hepatitis B as compared to those with chronic hepatitis B having a lesser CD4 increase (P = 0.03) [13]. In a cohort study in Denmark HBV infection sero-status is observed to have no effect on the response to HAART in terms of HIV viral load suppression and CD4 + cell count [3].…”
Section: Hepatitis B Virus Co-infection: Yet Another Reason For Earlymentioning
confidence: 97%